2019
DOI: 10.1542/hpeds.2019-0212
|View full text |Cite
|
Sign up to set email alerts
|

A Magic Therapy Program to Alleviate Anxiety in Pediatric Inpatients

Abstract: OBJECTIVES: Hospitalization generates increased psychological discomfort for children and their caregivers. This anxiety can affect the patient-caretaker response to the health care team and the course of treatment. We aim to evaluate the impacts of a magic therapy program, organized and facilitated by medical students, on alleviating pediatric inpatient and caregiver anxiety. METHODS: Patients aged 5 to 16 years admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…As reported, most trained students surveyed believed the therapy was useful for the child, parents, and staff. These findings are consistent with the previously reported opinions of physicians and nursing staff regarding MagicAid magic therapy [29] and show that students believe they are positively impacting others. Students remarked that they were able to "cheer…patients up" and that it was "good to see how happy patients" were after the interaction (Table 4).…”
Section: Meaning and Emotional Well-beingsupporting
confidence: 92%
See 2 more Smart Citations
“…As reported, most trained students surveyed believed the therapy was useful for the child, parents, and staff. These findings are consistent with the previously reported opinions of physicians and nursing staff regarding MagicAid magic therapy [29] and show that students believe they are positively impacting others. Students remarked that they were able to "cheer…patients up" and that it was "good to see how happy patients" were after the interaction (Table 4).…”
Section: Meaning and Emotional Well-beingsupporting
confidence: 92%
“…2). On previous surveys of health professionals, 97% of providers (predominantly nurses and resident physicians) reported that student magicians were not a disturbance to patient care [29]. We conclude that the novelty of patient care and lack of experience in the inpatient setting for preclinical medical students informed this misperception.…”
Section: Student Comfort In the Programmentioning
confidence: 70%
See 1 more Smart Citation
“…The results also showed a statistical reduction in Venham’s Picture test and modified visual analog scale (p=0.006 and 0.009, respectively). Similar anxiety reduction was observed in pediatric patients when magic therapy was given and evaluated using Venham’s Pictures test [ 8 ]. Also, Alparslan and Bozkurt found that the presence of medical clowns in hospitals reduces the child’s anxiety [ 15 ].…”
Section: Discussionmentioning
confidence: 56%
“…Reductions in fear and worry are particularly consistent with previous interventions targeting anxiety in hospitalized pediatric patients, including magic therapy. 15 Only a few researchers have investigated the physiologic effects of poetry on the human brain and body, and it is an area for further research. In one study, researchers found college-aged participants more relaxed after reading emotionally positive poems.…”
Section: Discussionmentioning
confidence: 99%